The relationships of sociodemographic factors, medical, psychiatric and substance-misuse comorbidities to neurocognition in short-term abstinent alcohol dependent individuals - Durazzo, Timothy C. (2008)
Comorbidies that commonly accompany those afflicted with an alcohol use disorder (AUD) may promote variability in the pattern and magnitude of neurocognitive abnormalities demonstrated. The goal of this study was to investigate the influence of several common comorbid medical conditions (primarily hypertension and hepatitis C), psychiatric (primarily unipolar mood and anxiety disorders), and substance use (primarily psychostimulant and cannabis) disorders, and chronic cigarette smoking on the neurocognitive functioning in short-term abstinent, treatment-seeking individuals with AUD. Seventy-five alcohol dependent participants (ALC; 51 ± 9 years of age; 3 females) completed comprehensive neurocognitive testing after approximately one-month of abstinence. Multivariate multiple linear regression evaluated the relationships among neurocognitive variables and medical conditions, psychiatric and substance use disorders, controlling for sociodemographic factors. Sixty-four percent of ALC had at least one medical, psychiatric or substance abuse comorbidity (excluding smoking). Smoking status (smoker or non-smoker) and age were significant independent predictors of cognitive efficiency, general intelligence, postural stability, processing speed and visuospatial memory after age-normed adjustment and control for estimated premorbid verbal IQ, education, alcohol consumption, and medical, psychiatric, and substance misuse comorbidities. Results indicated that chronic smoking accounted for a significant portion of the variance in the neurocognitive performance of this middle-aged AUD cohort. The age-related findings for ALC suggest that alcohol dependence, per se, was associated with diminished neurocognitive functioning with increasing age. The study of participants who demonstrate common comorbidities observed in AUD is necessary to fully understand how AUD, as a clinical syndrome, affects neurocognition, brain neurobiology, and their changes with extended abstinence.